A Scoping Review of Green-STEAM Education in Primary School Context - Rantanen, Sanna; Huang, Xiaoshan; Veermans, Marjaana (SAGE Publications, 2026)
STEAM education provides an interdisciplinary approach that fosters an understanding of sustainability and enhances real-world problem-solving, collaborative and inquiry skills. Given the absence of a comprehensive overview of STEAM with sustainability (G-STEAM) practices in primary school contexts, this scoping review conducts a thematic analysis to examine how sustainability is integrated into learning projects, covering learning topics, intended outcomes, pedagogical approaches and assessment tools. The findings emphasize a lack of STEAM projects promoting sustainability understanding. Projects are designed to enhance students’ twenty-first-century skills, subject knowledge, engaging learning experiences and sustainability knowledge and mindsets. Using diverse, constructive pedagogical approaches, these learning processes involve real-world problem-solving methods and integrated techniques to facilitate student reflection and abstraction. Assessment diversity is crucial for understanding student learning and promoting critical thinking, which are key for effective teaching. More research is needed to evaluate G-STEAM project alignment and effectiveness for evidence-based guidelines.